Evaluation of root morphology of maxillary and mandibular second molars lost due to periodontitis. (25th May 2020) - Kato, Akiko; Hishikawa, Toshimitsu; Inagaki, Koji; Yamamoto, Genta; Mitani, Akio; Honda, Masaki
Abstract: Background and objective: Little is known about the anatomical characteristics of root morphology in molars lost due to periodontal reason. The aim of this study was to study root morphology in maxillary and mandibular molars lost due to periodontitis by investigating the frequency of root fusion, classifying fusion types, and measuring radicular groove depth by micro‐computed tomography. Material and methods: Ninety‐eight posterior teeth were collected from 87 Japanese patients during the study period. Of these, maxillary (N = 36) and mandibular (N = 22) second molars lost most frequently were assessed for root fusion and morphology. Results: The 36 maxillary second molars included nine (25%) teeth with a single root, 14 (39%) with two roots, and 13 (36%) with three roots. Of the 23 maxillary second molars with fused (1 and 2) roots, there were 11 (48%), 2 (9%), 1 (4%), 1 (4%), 3 (13%), and 5 (22%) teeth with root types 1‐6, respectively. The 22 mandibular second molars comprised 14 (64%) teeth with a single root, 7 (32%) with two roots, and one (4%) with three roots. Of the 14 mandibular second molars with a fused (1) root, 12 (86%) had a C‐shaped root and two (14%) had a non‐C‐shaped root. Conclusion: We observed a higher frequency of root fusion in the present study compared with that reported by previous studies using randomly selected second molars.